PENGARUH PELATIHAN, PENDIDIKAN LANJUTAN, DAN PENGALAMAN MENGAJAR TERHADAP PENINGKATAN PROFESIONALISME GURU PRODUKTIF PADA SMK NEGERI DI KOTA MAKASSAR - Husnaeni; Muh. Nasir Malik; Hasanah Nur (UNM Journal of Technology and Vocational, 2023)
This study aims to examine the influence of training, further education, and teaching experience on teacher professionalism development. The study employed ex-post facto research method. The totalpopulation is 423 people, and the research sample is 112 people, who obtained by employingpurposive sampling technique. Data collection employed documentation and questionnaire. Theprerequisite test employed the data normality test, data linearity test, data multi-collinearity test, anddata heteroscedasticity test. The results of the descriptive analysis indicate that training, furthereducation, and teaching experience have contributed to productive teacher professionalismdevelopment at public vocational schools in Makassar city, which is in very high category. Based onthe hypothesis test using a simple linear regression test and multiple linear regression test, it isdiscovered that: (1) there is a significant influence between training and productive teacherprofessionalism development at public vocational schools in Makassar city. The test results show thatthe sig. is 0.000 < 0.05 with a contribution of 33.1%, (2) there is a significant influence betweenfurther education and productive teacher professionalism development at public vocational schools inMakassar city. The test results show that the sig. is 0.000 < 0.05 and has an influence of 31.3%, (3)there is a significant influence between teaching experience and productive teacher professionalismdevelopment at public vocational schools in Makassar city. The test results show that the sig. is 0.000< 0.05 and has an influence of 46.4%, and (4) the training, further education, and teachingexperience collectively have an influence on productive teacher professionalism development atpublic vocational schools in Makassar city. The test results show that the sig. is 0.000 < 0.05 and hasan influence of 50.6%.